Editorial Foreword - Ab Gani, Muhamad Abdul Aziz; Ramli, Ishak`; Yahaya, Mohamad Hafiz; Taharuddin, Nurul Shima; Md Nazri, Haslinda; Rosman, Muhammad Redza; Nazrin, Nizar (Idealogy Journal, 2019)
We are very pleased that Idealogy Journal of Arts and Social Science is presenting its 4th volume and 2nd issue. We are also very excited that the journal has been attracting papers from a variety of advanced and emerging countries such as Indonesia, Pakistan, Saudi Arabia, Bangladesh, etc. The variety of submissions from such countries will help the aimed global initiatives of the journal. We are also delighted that the researchers from the Arts and Social Science fields demonstrate an interest to share their research with the readers of this journal. This issue of Journal of Arts and Social Science contains five outstanding articles which shed light on contemporary research questions in arts and social science fields. Keyword:  Journal Foreword